2000
DOI: 10.1542/peds.105.6.e83
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adolescent Physical Activity and Inactivity Patterns

Abstract: ABSTRACT. Objectives. Despite recognition of the important influence of environmental determinants on physical activity patterns, minimal empirical research has been done to assess the impact of environmental/ contextual determinants of physical activity. This article aims to investigate environmental and sociodemographic determinants of physical activity and inactivity patterns among subpopulations of US adolescents. We define environmental determinants as modifiable factors in the physical environment that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
497
10
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 763 publications
(580 citation statements)
references
References 31 publications
50
497
10
23
Order By: Relevance
“…In addition, the positive association between inactivity and OW is weakened when the multivariate model is adjusted for SES, which is not the case for LTPA. Gordon-Larsen et al (2000) support the hypothesis according to which physical activity and inactivity are influenced by different determinants. Their analyses in a national sample of American adolescents led to the conclusion that physical activity was most influenced by environmental factors, such as participation in school physical education programs and the use of neighbourhood community recreation centres.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the positive association between inactivity and OW is weakened when the multivariate model is adjusted for SES, which is not the case for LTPA. Gordon-Larsen et al (2000) support the hypothesis according to which physical activity and inactivity are influenced by different determinants. Their analyses in a national sample of American adolescents led to the conclusion that physical activity was most influenced by environmental factors, such as participation in school physical education programs and the use of neighbourhood community recreation centres.…”
Section: Discussionsupporting
confidence: 81%
“…Gordon-Larsen et al (2005; also find similar results and suggest that this is due to poor neighborhood quality, and lack of good recreational facilities in areas with a high fraction of African-American population. Our results also indicate higher levels of physical activity participation among teenagers residing in highly populated Asian areas, though this result is not very statistically significant even in the SCHBL model.…”
Section: Zonal Structure Density and Race Composition Variablessupporting
confidence: 58%
“…Social and cultural dietary behaviors must be taken into account when environmental effects are studied in any population. 49 The lack of relationship between density of parks and public sport facilities and leisure physical activity also contrasts with the results of many US studies that showed a positive association among both adolescents 50,51 and adults. [52][53][54] However, we did find areas with higher concentration of parks and public sports facilities, located at the central and wealthier areas of the city, with lower rates of overweight, even after adjusting by area SES.…”
Section: Discussionmentioning
confidence: 76%